Artificial Intelligence and Evolutionary Computations in Engineering Systems Proceedings of ICAIECES 2015 - Dash, Subhransu Sekhar; Bhaskar, M. Arun; Panigrahi, Bijaya Ketan; Das, Swagatham (Advances in Intelligent Systems and Computing, 2016)
The book is a collection of high-quality peer-reviewed research papers presented in the first International Conference on International Conference on Artificial Intelligence and Evolutionary Computations in Engineering Systems (ICAIECES -2015) held at Velammal Engineering College (VEC), Chennai, India during 22 - 23 April 2015. The book discusses wide variety of industrial, engineering and scientific applications of the emerging techniques. Researchers from academic and industry present their original work and exchange ideas, information, techniques and applications in the field of Communication, Computing and Power Technologies.